Coal Prices in Poland: Is the Domestic Market Separated from the International Market? - Rembeza, Jerzy (International Journal of Energy Economics and Policy, 2020)
The paper presents the relationships between coal prices on the domestic market in Poland and prices of coal and natural gas on the international market. The analyses use the ARDL model. Long-term linkages were analysed with the bounds test, while short-term adjustments - with unconditional ECM models. The obtained results indicate a clear hierarchy of markets. Coal prices on the Polish market were not cointegrated with natural gas prices and they were relatively poorly integrated with coal prices on the international market. Coal prices exported from Poland and international prices were connected more strongly. The strongest relationships were stated between coal and gas prices on the international market. At that level, coal prices behaved in a manner characteristic to the global market. Keywords: Coal, prices, integration, international market, domestic market, Poland JEL Classifications: C22, F14, Q41 DOI: https://doi.org/10.32479/ijeep.9393